Rarely Seen Poland–Moebius Syndrome: A Comprehensive View with Perspective of Pediatric Neurology - Havalı, Cengiz; Saymazlar, Dilek Damla; Öztürk, Zeynep (Journal of Pediatric Neurology, 2020)
Background Moebius syndrome is a rare congenital disorder characterized by a unilateral or bilateral congenital facial weakness with impairment of ocular movements. Poland syndrome is an occasional disease defined as the unilateral absence of pectoralis major muscle and ipsilateral syndactyly. As to, Poland–Moebius syndrome is a rare condition which consists of assembly components of Poland and Moebius syndromes.Patients and Methods Patient 1 is a 12-year-old male patient referred for evaluation of difficulties in eye movements to the hospital. On admission, facial, abducens, trochlear, and oculomotor cranial nerves involvement was determined in the neurological examination. His right pectoralis major muscle was hypoplastic in the examination. Patient 2 is a 4-month-old female patient who was admitted with restricted eye movements, weakness of crying, and difficulty in swallowing. Neurological examination indicated facial, abducens, trochlear, oculomotor, glossopharyngeal, and vagus cranial nerves involvement. Her physical examination demonstrated hypoplastic left pectoralis major muscle and hypoplastic left hand.Results The biochemical laboratory studies, creatinine kinase levels, and tests for inborn error of metabolism of both patients were normal. Chest X-ray studies revealed the lack of muscle tissue development in the left pectoral region. Cranial magnetic resonance imaging, echocardiography, and abdominal ultrasound were also normal.Conclusion This report highlights two cases of Poland–Moebius syndrome in two patients of varying age and clinical presentations, with a comprehensive review from the perspective of pediatric neurology.
Keywords: Moebius syndrome; Poland syndrome; facial weakness; ophthalmoplegia